Mutational evaluation of TP53 gene in the canine hepatocellular carcinoma: a comparative approach - Gomez, David Salas (2019)
Hepatocellular carcinomas (HCC) represent an important part of hepatic diseases in dogs, correspond to more than 50% of primary neoplasms of the liver in this species. HCC affects, mainly, male dogs over 10-years-old, presenting poor prognosis in patients not suitable for surgery. Latest years, studies about comparative oncology have acquired great importance, since dogs and humans share diverse cellular and molecular features. In humans, HCC is associated with chronic liver injuries, caused by viral infections (hepatitis C and B), fatty liver disease (alcoholic and non-alcoholic), chronic intoxication (drugs, mycotoxins, etc.), among others. The consumption of aflatoxin B1 (AFB1) is associated with a specific mutation in codon 249 of the TP53 gene, causing HCC in part of the patients exposed to this mycotoxin. In case that dogs do not present chronic viral hepatitis or fatty liver diseases, environmental and feeding factors, such as the possible presence of aflatoxin B1 in pet food, may be directly related to the etiology of HCC in this species. Firstly, this study performed a comparative literature review of epidemiological, clinicopathological and anatomopathological aspects of HCC in dogs and humans. Subsequently, the presence of mutations in the TP53 gene were evaluated in canine HCC samples (n = 24), in order to determine a possible association of AFB1 in hepatocarcinogenesis. Clinicalepidemiological data observed in canine HCC are in agree with the literature reviewed. However, mutations in the TP53 gene or p53 immunoexpression were not observed. Thus, due to the absence of mutations in the TP53 gene in the analyzed samples, the participation of AFB1 as an etiological factor in HCC remains open.